2015
DOI: 10.1515/cmble-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

How taste works: cells, receptors and gustatory perception

Abstract: The sensitivity of taste in mammals varies due to quantitative and qualitative differences in the structure of the taste perception organs. Gustatory perception is made possible by the peripheral chemosensory organs, i.e., the taste buds, which are distributed in the epithelium of the taste papillae of the palate, tongue, epiglottis, throat and larynx. Each taste bud consists of a community of ~100 cells that process and integrate taste information with metabolic needs. Mammalian taste buds are contained in ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 84 publications
(123 reference statements)
0
36
0
Order By: Relevance
“…It is well known that sourness strongly relates to pH [19]. Our previous report indicated that saliva pH affects sweetness sense [10].…”
Section: Discussionmentioning
confidence: 89%
“…It is well known that sourness strongly relates to pH [19]. Our previous report indicated that saliva pH affects sweetness sense [10].…”
Section: Discussionmentioning
confidence: 89%
“…Taste buds consist of elongated taste cells and round basal cells. Taste cells are divided into 3 types; types I-III [Roper, 2013;Taruno et al, 2013;Kikut-Ligaj and Trzcielińska-Lorych, 2015]. Type I taste cells have oval nuclei and are considered to be associated with transmitter clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Taste dysfunction and other oral complications after irradiation (i.e., xerostomia, mucositis) lead to decreased appetite and life quality, thereby affecting the treatment outcome of these patients (Yamashita et al., ). Taste buds are the gustatory organs that mediate the sense of taste by taste cells (Kikut‐Ligaj & Trzcielinska‐Lorych, ). Accumulating evidence shows that the impairment of basal and differentiated taste cells in taste buds is the main cause of radiotherapy‐induced taste dysfunction (Yamazaki, Fujii, & Ochiai, ).…”
Section: Introductionmentioning
confidence: 99%